Horseshoe crab bio-ecological data from Balok, East Coast Peninsular Malaysia - Mat Zauki, Nurul Ashikin; Satyanarayana, Behara; Fozi, Nur Fairuz; Nelson, Bryan Raveen; Martin, Melissa Beata; John, Akbar; Khan Chowdhury, Ahmed Jalal (Elsevier Inc., 2019)
The data available in this repository were gathered from Balok, the only most productive spawning site for horseshoe crabs Tachypleus gigas and Carcinoscorpius rotundicauda in East Coast of Peninsular Malaysia. The mangrove horseshoe crab, C. rotundicauda population and spawning data are available in the first table. The horseshoe crabs were retrieved from Balok River using 11.43 cm mesh size gill nets installed at the river mouth, the confluence and last meander. The arthropods were inspected for damage, abnormality and growth before their release into Balok River, particularly at the site of capture. Sediment samples were retrieved at their spawning grounds to ascertain sediment composition and size classifications which were also processed using Logarithmic Method of Moments. Water parameters like temperature, pH and salinity were also investigated during year 2016. All these information are compiled into the second table and arranged according to the period of data availability. The horseshoe crab catch data of years 2012, 2013, 2014, 2015 and 2016 were made available by artisanal fisher and compiled in the third and fourth table for inter-species comparison.